OPEN CHOLECYSTECTOMY WITHOUT INTRAPERITONEAL DRAINAGE - Ali, Syed Asad; Tahir, Syed Muhammad; Soomoro, Abdul Ghani; Siddiqui, Akmal Jamal; Memon, Abdul Sattar (Journal of Ayub Medical College Abbottabad, 2010)
Background: Cholecystectomy through laparotomy with or without intra-peritoneal drain has been the standard operation for the gall bladder disease for the last 100 years. It implies removal of gall bladder and is performed mainly for symptomatic gall stones. The Objectives was to analyse the outcome of open cholecystectomy without drain in term of complications. Methods: Patients who underwent open cholecystectomy without drainage from January 2005 to December 2008, at Department of Surgery, Liaquat University Hospital, Jamshoro, Pakistan were included in the study. This was a 4 years prospective analysis of open cholecystectomy performed without drainage on 212 patients. Patients were randomly allocated for the procedure who presented with uncomplicated Cholelithiasis. Exclusion Criteria included carcinoma gall bladder, empyema gall bladder, Choledocholithiasis and porcelain gall bladder. All these patients underwent open cholecystectomy under general anaesthesia through various incisions. Operative time, post operative complications and hospital stay were recorded on a performa and analysed using SPSS-13. Results: Two hundred and twelve patients, 199 females (93.9%) and 13 males (6.13%), age range 15 to 70 years, underwent open cholecystectomy without drainage for uncomplicated cholelithiasis. The most common complication observed includes seroma (5.66%), followed by surgical site infection both superficial and deep (3.30%) and bile leakage (1.14%). However biliary peritonitis, sub hepatic abscess and Wattman Walter’s syndrome were not observed in any case. Mean operating time was 35 minutes. Mean hospital stay was 1.5 days with no mortality during the period of hospitalisation. The overall complications rate and hospital stay was significantly less when compared to open cholecystectomy with intra-peritoneal drain. Conclusion: In selected cases with a dry gall bladder bed, routine use of intra peritoneal drainage is unnecessary. Keywords: open cholecystectomy, intra peritoneal drain, complications